Comparison of the oropharyngeal leak pressure between three second generation supraglottic airway devices during laparoscopic surgery in pediatric patients. Issue 7 (5th April 2022) - Kumar, Abhyuday; Sinha, Chandni; Kumar, Neeraj; Kumar, Ajeet; Kumar, Bindey; Kumar, Amarjeet; Kumar, Rajnish
Abstract: Background: Previous studies have shown Proseal LMA and I gel similar to endotracheal intubation in ventilatory ability in pediatric laparoscopic surgeries. Aims: The primary aim of this study was to assess whether there is a significant difference in the oropharyngeal leak pressure between Ambu Auragrain, I‐gel, and Proseal LMA during pediatric laparoscopic surgery. Methods: In this randomized controlled trial, 90 male patients of American Society of Anesthesiologists physical status I aged between 6 months and 10 years who were scheduled for laparoscopic single‐sided inguinal hernia repair were recruited and randomly allocated to three groups in which airway was secured with Ambu Auragain, I gel, or Proseal LMA. The primary outcome was oropharyngeal leak pressure. The secondary outcomes were peak pressures before and after pneumoperitoneum, fiberoptic view, insertion attempts, insertion time, manipulations, perioperative and postoperative anesthesia‐related problems. Continuous variables were compared using the one‐way analysis of variance or the Kruskal–Wallis test with post hoc Turkey analysis. Categorical and ordinal data were compared using the chi‐square test or Fisher's exact test. Results: Oropharyngeal leak pressure before pneumoperitoneum was higher with I gel as compared to Ambu Auragain (27.36 ± 5.72 cm of H2 O vs 23.56 ± 5.72 cm of H2 O) ( p = .021) and PLMA (27.36 ± 5.72 cm of H2 O vs 23.24 ± 4.35 cm of H2 O) ( p = .011). Oropharyngeal leak pressure after pneumoperitoneum was also higher with I gel as compared to Ambu Auragain (31.58 ± 4.35 cm of H2 O vs 26.83 ± 5.00 cm of H2 O) ( p = .001) and Proseal LMA (31.58 ± 4.35 cm of H2 O vs 27.03 ± 3.80 cm of H2 O) ( p = .002). Oropharyngeal leak pressures of Ambu Auragain and Proseal LMA were comparable. Postoperative complications were similar in all the supraglottic airway devices. No regurgitation or aspiration‐related problem was observed in our study. Conclusion: I gel had a higher oropharyngeal leak pressure than the other two supraglottic airway devices and therefore may represent a better choice in situations where higher ventilatory pressures may be necessary, for example, in extremes of weight trendelenburg position, etc. Clinical Trial Identifier: Clinical trial registry of India (CTRI/2018/11/016445).